Honey and cancer: from traditional medicine to modern adjuvant therapy - Kmail, Abdalsalam (Frontiers in Oncology, 2026)
Cancer remains one of the principal causes of death worldwide, with conventional treatments like chemotherapy and radiotherapy often exhibiting high toxicity, resistance, and relapse rates. These constraints have sparked new investigation of bioactive phytochemicals as complements to standard therapies, in an attempt to increase efficacy and reduce toxicity. Honey, an ancient natural product used in ethnomedicine, has been the focus of recent attention due to its multifactorial biochemical composition and possible anticancer properties. This review aggregates recent research on honey’s anticancer activities, describing its molecular mechanisms—including caspase-mediated apoptosis, cell cycle regulation, reduction of NF-κB and STAT3 activity, and metastasis prevention. We review preclinical studies in various cancer models, highlighting honey’s ability to sensitize tumors to chemotherapy. Finally, we review clinical data on honey’s ability to relieve therapy-induced side effects such as mucositis and hematologic suppression. In spite of promising data, issues remain about standardizing its active components, pharmacokinetics, and lack of large scale human trials. This review supports honey’s incorporation into evidence-based oncology paradigms pending additional robust validation.